In favour of moral reflection and against codes of conduct in Social Work - Rodríguez Alcázar, Javier (Cuadernos de Trabajo Social, 2016)
This article first argues that moral philosophy can assist social workers to enrich their reflections on practice and to refine their judgments when choosing their own style of professional action. But this article also maintains that professional codes of conduct do not make an adequate contribution to these aims, and that other benefits generally attributed to such codes, including strengthening of identity and professional prestige, would be better achieved by means of other documents summarizing the dominant political stances of the profession in a given time and place. The theoretical basis for these arguments is provided by Bernard Williams’ criticism of political moralism —understood as the attempt to subordinate politics to moral ends and judgments— and my own proposal of political minimalism, which incorporates an understanding of the relationship between ethics and politics in terms of «reciprocal inclusion».